Earth Observation in the EMMENA Region: Scoping Review of Current Applications and Knowledge Gaps - Marinos, Eliades; Silas, Michaelides; Evagorou, Evagoras S.; Fotiou, Kyriaki; Fragkos, Konstantinos; Leventis, Georgios; Theocharidis, Christos; Panagiotou, Constantinos F.; Mavrouvoniotis, Michalis; Neophytides, Stelios; Papoutsa, Christiana; Neocleous, Kyriacos; et al. (My University, 2023)
Earth observation (EO) techniques have significantly evolved over time, covering a wide range of applications in different domains. The scope of this study is to review the research conducted on EO in the Eastern Mediterranean, Middle East, and North Africa (EMMENA) region and to identify the main knowledge gaps. We searched through the Web of Science database for papers published between 2018 and 2022 for EO studies in the EMMENA. We categorized the papers in the following thematic areas: atmosphere, water, agriculture, land, disaster risk reduction (DRR), cultural heritage, energy, marine safety and security (MSS), and big Earth data (BED); 6647 papers were found with the highest number of publications in the thematic areas of BED (27%) and land (22%). Most of the EMMENA countries are surrounded by sea, yet there was a very small number of studies on MSS (0.9% of total number of papers). This study detected a gap in fundamental research in the BED thematic area. Other future needs identified by this study are the limited availability of very high-resolution and near-real-time remote sensing data, the lack of harmonized methodologies and the need for further development of models, algorithms, early warning systems, and services.
Keywords: Eastern Mediterranean; Middle East; EMMENA); North Africa; atmosphere; water; agriculture; land; disaster risk reduction; cultural heritage; energy; marine safety and security; Big Earth Data